MEWUJUDKAN SWASEMBADA AIR DAN PANGAN DI PONDOK PESANTREN RIYADHUT TAFSIR MELALUI TEKNOLOGI SUMUR BOR, SISTEM FILTRASI, DAN BUDIDAYA LELE BIOFLOK - Mirnayani, Mirnayani; Suwandari, Yunita Dian; Hanum, Bethriza; Novianto, Rizqi Hadi; Fauzi, Alva Azmi (Jurnal Abdi Insani, 2025)
Riyadhut Tafsir Islamic Boarding School in Parung Panjang, Bogor, faces limited access to clean water and remains dependent on external food supplies. This condition hampers students’ daily activities, especially during the dry season when water is scarce. The available water was not suitable for consumption due to the absence of filtration. Food problems also emerged since self-sufficiency in cultivation had not been achieved optimally. The aim of this activity is to enhance the self-sufficiency of the boarding school through appropriate technology, namely bore wells, a filtration system, and biofloc catfish cultivation. The methods included needs assessment, system design, implementation of bore well and filtration technology, construction of biofloc ponds, and training students in clean water management and fish farming. In addition, a pre test and post test were conducted to measure participants’ competency improvement. The results showed significant improvements in water availability, with a bore well discharge reaching 1.2 L/s, water quality improvement with turbidity reduced and pH stabilized at 7.1–7.4 after filtration. The boarding school now has 3 biofloc ponds with a capacity of 100 fish each, achieving a catfish survival rate of 95% after two months of cultivation. Knowledge evaluation results showed an average score increase from 25.0 (pre test) to 90 (post test), with all participants achieving the minimum competency standard of ≥75. Students were actively involved in maintenance, which significantly enhanced their technical skills. In conclusion, the application of bore well technology, a filtration system, and biofloc ponds successfully improved water and food self-sufficiency while effectively enhancing students’ competencies through appropriate technology-based training.